Electrochemical detection of bisphenols in food: A review. (1st June 2021) - Zhang, Yuhuan; Lei, Yanan; Lu, Hao; Shi, Lin; Wang, Peng; Ali, Zeshan; Li, Jianke
Highlights: The usage and harmful effects of bisphenols (BPs) on human bodies are discussed. Four kinds of electrochemical BPs sensors are summarized according to their recognition elements. The similarities and differences between difference electrochemical BPs sensors are deeply discussed. Abstract: Bisphenols (BPs) are worldwide used organic compounds in plastics, belonging to the group of endocrine disrupting chemicals (EDCs) which exhibits endocrine disruption to beings. Migration of BPs from food contact materials like plastic containers, epoxy coatings in metal cans and thermal papers, would results in bioaccumulation of BPs in human beings, causing adverse health effects. Therefore, sensitive and selective determination of BPs in food is needed. Among different strategies have been explored for the detection of BPs, electrochemical sensors with relatively high sensitivity and fast response are promising. This paper is devoted to comprehensively review the developed electrochemical methods for BPs sensing in food, so that to find a direction for developing low cost, high accuracy and compatibility sensors toward the sensitive and selective detection of BPs. Different electrochemical technologies categorized by recognition agents, aptamers, enzymes, molecularly imprinted polymers and nanomaterials are discussed and summarized in their mechanisms, usages, merits and limitations. The challenges and further perspectives in the development of electrochemical sensors is also discussed.